(untitled) (Academicia Globe: Inderscience Research, 2023)
The present study was conducted as an attempt to chemically treat secondary hydatid disease in white mice of Mus musculus strain Balb/c by Immunity Boost used Immunomodulators, including antioxidant by used immunological test for example Delayed type hypersensitivty reaction (DTH), Phagocytosis, Micronucleus assay, Agar gel immune diffusion assay.